Prevalence of motor disorders and repetitive movements among children with Autism spectrum disorders and Tics disorders - Dubovyk, Kostiantyn (Psychosomatic Medicine and General Practice, 2018)
Background. Children with autism spectrum disorders (ASD) have difficulties in the development of simulating, gross and fine motor skills, hand-eye coordination and language skills. Tics and repetitive movements often associated with ASD, intellectual deficiency. Aim. To identify a relationship between tic disorders and specific developmental disorders: motor skills, speech, cognitive functions in children with ASD. Methods. There were randomized 79 children aged 4-6 years with ASD, 38 children among them with comorbid tics disorders (TD). For the diagnosis of ASD were used diagnostic criteria of ICD-10, Autism Diagnostic Interview-Revised (ADI-R), Autism Diagnostic Observation Schedule (ADOS). The development of motor skills, speech, and cognitive function was assessed using Psycho-educational Profile (PEP-R). For the diagnosis of comorbid mental disorders ware conducted using The Development and Well-Being Assessment (DAWBA). As motor disorders considered tics, abnormal movements associated with ADHD, anxiety and obsessive-compulsive disorders. Tics were assessed by Yale Global Tic Severity Scale (YGTSS). Results. In children with ASD and comorbid TD was noted retardation of formation of gross motor skills in comparison with the control group by PEP-R. It was also noted delay in the formation of skills in receptive speech and gross motor skills in accordance with the results of evaluation by using Vineland-II.